(untitled) (Revista Rupturas, 2022)
This article aims to decipher and question the moral stances that stand out, nowadays, among Costa Ricans, regarding sexuality—premarital sex, divorce, homosexuality, and abortion. This approach is based on the data reported in the survey “Perceptions in Costa Rican Society About Values and Religious Practices”, which was carried out by the Institute of Social Studies on Population (IDESPO) and the Epistemic Community of Socio-Religious Studies from the National University of Costa Rica (UNA), in October 2018. The study provides an account of the different moral stances that coexist in Costa Rica, and it seeks to explain such stances in the light of variables such as religious affiliation, sex, age, and educational attainment.